Proteomics in cancer research (Wiley & Sons, 2005)
The unique proteomic features that characterize cancers offer new opportunities for disease prevention and treatment. Despite intense interest, however, proteomics is just beginning to become a part of the cancer research mainstream, as relatively few cancer researchers have training in proteomics methods and approaches. This book, therefore, is both a timely and an essential guide that will help readers understand key concepts of proteomics and use its methods to search for ways to both cure and prevent cancer.